KOMUNIKASI KELOMPOK DALAM MEMBANGUN PERSEPSI PETANI TERHADAP PROGRAM ASURANSI USAHA TANI (AUTP) DI KABUPATEN LOMBOK BARAT - I Nyoman Sunetrayana; I Wayan Wirata; Ni Putu Listiawati (Widya Sandhi, 2021)
The aim of this study is to analyze the benefits of group communication in building farmers' perceptions of the AUTP program; to analyze the factors that influence group communication in building farmers' perceptions of the AUTP program; and to analyze how to encourage effective group communication in building farmers' perceptions of the AUTP Program in West Lombok Regency. This study uses a descriptive method with a qualitative approach. Data were collected through observation: observations and interview methods. Analysis of the research data showed that 66,7% of farmers gave a positive perception of the AUTP program because of the establishment of effective communication within the group so as to increase the confidence of farmers (based on the assessment of 73,3% of farmers). As many as 66% of farmers considered that experienced extension workers have the ability to build group communication so that they can build positive farmer perceptions of the AUTP program. The intense knowledge transfer process from the extension workers takes place in group communication so that it stimulates stimulation to farmers and causes a response in the form of a very good perception of the AUTP program.